Phenotypic and functional modulation of 20–30 year old dermal fibroblasts by mid- and late-gestational keratinocytes in vitro. Issue 5 (August 2015) - Wang, Zhe; Liu, Xiaoyu; Zhang, Dianbao; Wang, Xiliang; Zhao, Feng; Zhang, Tao; Wang, Rui; Lin, Xuewen; Shi, Ping; Pang, Xining
Highlights: Mid-gestational KCs exert a positive effect on proliferation and migration in fibroblasts. Mid-gestational KCs exert a positive effect on collagen synthesis in fibroblasts. Mid-gestational KCs exert a positive effect on ECM remodeling in fibroblasts. The positive effect is mediated by a variety of molecules. Abstract: Fetal wound healing occurs rapidly and without scar formation early in gestation, but the mechanisms underlying this scarless healing are poorly understood. This study explores the phenotypic and functional modulation of 20–30 year old dermal fibroblasts by mid- and late-gestational keratinocytes (KCs) in vitro. Human KCs of different gestational ages were isolated, characterized, and co-cultured with human 20–30 year old fibroblasts. Gene expression and protein levels of TGF-β family members, precollagen, collagen, matrix metalloproteinases (MMPs), and the tissue inhibitors of metalloproteinases (TIMPs) were measured in the fibroblasts. Mid-gestational KCs promoted faster proliferation and migration of fibroblasts than late-gestational KCs. Additionally, significant differences in gene expression and protein levels of some markers were observed in fibroblasts co-cultured with mid- or late-gestational KCs. Fibroblasts co-cultured with mid-gestational KCs for 48 h exhibited downregulated gene expression of precollagen 1, collagen 1, TGF-β1, TGF-β2, TIMP-2 and TIMP-3, while precollagen 3, collagen 3, TGF-β3, and MMP-1, -2, -3, -9 and -14 were upregulated. In contrast, late-gestational KCs exhibited downregulated TIMP-1, TIMP-2 and TIMP-3 levels, while collagen 1, TGF-β2, TGF-β3, and MMP-2, -3, -9 and -14 were upregulated. Moreover, statistically significant differences in expression levels of precollagen 1, precollagen 3, collagen 1, TGF-β1, -β2, and -β3, MMP-1, -3 and MMP-14, TIMP-1 and TIMP-2 were found between fibroblasts co-cultured with mid- and late-gestational KCs. Furthermore, cytokine levels of IL-1a and HB-EGF were found to be statistically different between conditioned medium from mid- and late-gestational KCs. Therefore, the gestational age of KCs appears to have an important effect on scarless wound healing in the human fetus.